Acute Plasmodium berghei Mouse Infection Elicits Perturbed Erythropoiesis With Features That Overlap With Anemia of Chronic Disease - Lakkavaram, Asha; Lundie, Rachel J.; Do, Hang; Ward, Alister C.; de Koning-Ward, Tania F. (Frontiers in Microbiology, 2020)
Severe malaria anemia is one of the most common causes of morbidity and mortality arising from infection with P. falciparum. The pathogenesis of malarial anemia is complex, involving both parasite and host factors. As mouse models of malaria also develop anemia, they can provide a useful resource to study the impact of Plasmodium infections and the resulting host innate immune response on erythropoiesis. In this study, we have characterised the bone marrow and splenic responses of the erythroid as well as other hematopoietic lineages after an acute infection of Balb/c mice with Plasmodium berghei. Such characterization of the hematopoietic changes is critical to underpin future studies, using knockout mice and transgenic parasites, to tease out the interplay between host genes and parasite modulators implicated in susceptibility to malaria anemia. P. berghei infection led to a clear perturbation of steady-state erythropoiesis, with the most profound defects in polychromatic and orthochromatic erythroblasts as well as erythroid colony- and burst-forming units (CFU-E and BFU-E), resulting in an inability to compensate for anemia. The perturbation in erythropoiesis was not attributable to parasites infecting erythroblasts and affecting differentiation, nor to insufficient erythropoietin (EPO) production or impaired activation of the Signal transducer and activator of transcription 5 (STAT5) downstream of the EPO receptor, indicating EPO-signalling remained functional in anemia. Instead, the results point to acute anemia in P. berghei-infected mice arising from increased myeloid cell production in order to clear the infection, and the concomitant release of pro-inflammatory cytokines and chemokines from myeloid cells that inhibit erythroid development, in a manner that resembles the pathophysiology of anemia of chronic disease.